IMPLEMENTASI PENDIDIKAN KARAKTER PADA LEMBAGA PENDIDIKAN FORMAL MENURUT KAJIAN FILSAFAT PROGRESIVISME - Siti Khomairroh,; Muhammad Nurwahidin,; Sudjarwo, Sudjarwo (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The flow of progressivism is the basic foundation to build the foundation in the application of character education. The flow of progressivism philosophy brings a concept of change in order to develop potential, and provide solutions for problem solving which we can later apply to design various types of basic values of character education in formal educational institutions in Indonesia. This study has the intent and purpose to explain how the concept of implementing character education in formal educational institutions in the study of the philosophy of progressivism. The method used is Literature Review. The references used were obtained from databases published in Indonesian journals in 2018-2022. The results of this study (1) Indonesian education is currently related to the concept of progressivism, starting from the implementation of an independent curriculum that is relevant to the concept of progressivism according to John Dewey; (2) the application of the flow of progressivism in character education can be done by providing examples/examples from the teacher to students, because the character and personality of the teacher can reflect the character and personality of the students themselves; (3) students are given guidance and accompanied by teachers according to their ability to develop themselves so that a great and strong character is formed.